A TRAV26‐1‐encoded recognition motif focuses the biased T cell response in celiac disease. Issue 1 (30th October 2019) - Frick, Rahel; Gunnarsen, Kristin Støen; Dahal‐Koirala, Shiva; Risnes, Louise Fremgaard; Sollid, Ludvig M.; Sandlie, Inger; Høydahl, Lene Støkken; Løset, Geir Åge
Abstract : The semi‐public T‐cell response towards the gluten epitope DQ2.5‐glia‐α2 uses a prototypic TCR encoded by the germline segments TRAV26‐1 and TRBV7‐2 . Through mutagenesis experiments, we show that a TRAV26‐1 encoded recognition motif contacts the MHC β‐chain and the TCR CDR3β loop underpinning this conserved T‐cell response restricted to the prototypic TCRs.